EFFECT OF CRYSTALLOID FLUID LOADING AND VASOPRESSOR PRE-TREATMENT ON THE TIME OF BLOOD PRESSURE DROP IN CESAREAN SECTION WITH SUBARACHNOID BLOCK - Muhammad Irfan Djafar; Andi Salahuddin; Syafruddin Gaus (Jurnal Kesehatan, 2022)
Caesarean section (SC) is the most frequently performed surgery in obstetrics. Subarachnoid block (SAB) and epidural block are the most widely used anesthetic techniques in CS surgery. Objectives To analyze the effect of loading crystalloid fluid and administration of vasopressors on the time of occurrence of a decrease in blood pressure in SC with SAB anesthesia. Method single-blind randomized controlled clinical trial consisting of 2 treatment groups, namely crystalloid fluid loading and vasopressor pre-treatment. The Results There was a significant difference in mean blood pressure between the crystalloid group and the vasopressor group at 2 to 8 minutes (p<0.05). The average systolic blood pressure for 46 minutes in the three groups showed that the decrease in blood pressure occurred first in the crystalloid group compared to the vasopressor group, and hypotension occurred at 5 minutes in the crystalloid group. After the first 10 minutes, average blood pressure tends to be relatively stable. There was a significant difference in the incidence of hypotension, which occurred more in the crystalloid group, which was 9 or 45%, the vasopressor group with hypotension was 2 or 10% (p<0.05). The incidence of decreased blood pressure was found to be more common with crystalloid loading than with vasopressor pretreatment, in accordance with the findings of previous studies. The incidence of decreased blood pressure in SC with SAB anesthesia was faster and more common with loading crystalloids than pretreatment with vasopressors. Administration of vasopressor pretreatment has been shown to prevent the incidence of a decreased blood pressure in SAB anesthesia.